Frequency security constrained control of power electronic‐based generation systems. Issue 10 (2nd May 2021) - Steinkohl, Joachim; Peyghami, Saeed; Wang, Xiongfei; Davari, Pooya; Blaabjerg, Frede
Abstract: Power grids with high integration of power electronic converters face new issues that have not existed before. The frequency in the power system is highly related to the inertia and the rotational speed of the operational synchronous machines. This is now changing, as the converter‐based generation units are contributing increasingly to the balancing of active power in the modern power grid. Several frequency control designs for the power electronic‐based generation units have been presented in the past. However, optimal control structures and settings are dependent on the current power grid parameters and operation. The converter‐based units allow the transmission system operators to change their behaviour according to their grid requirements much more dynamical than ever before. The paper proposes a new analysis framework that can be utilized to find the best‐suited control settings in converter‐based units to enhance the system frequency reliability. The proposed framework is demonstrated in a study case by varying the settings of one frequency control scheme currently used in wind power plants in the Danish grid codes and validated on the IEEE 24‐Bus reliability test system with additional wind power integration.